2021
DOI: 10.1093/nar/gkab657
|View full text |Cite
|
Sign up to set email alerts
|

Wnt target enhancer regulation by a CDX/TCF transcription factor collective and a novel DNA motif

Abstract: Transcriptional regulation by Wnt signalling is primarily thought to be accomplished by a complex of β-catenin and TCF family transcription factors (TFs). Although numerous studies have suggested that additional TFs play roles in regulating Wnt target genes, their mechanisms of action have not been investigated in detail. We characterised a Wnt-responsive element (WRE) downstream of the Wnt target gene Axin2 and found that TCFs and Caudal type homeobox (CDX) proteins were required for its activation. Using a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 95 publications
0
26
0
Order By: Relevance
“…We then tested the contribution of SOX sites for WRE activation by mutating them in the c-Myc-335-luc reporter. Previously, we found that mutating the 4 TCF sites caused a reduction in enhancer activity ( 9 ). Mutating either one of the SOX sites caused a reduction in enhancer activity comparable to mutating the 4 TCF binding sites.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We then tested the contribution of SOX sites for WRE activation by mutating them in the c-Myc-335-luc reporter. Previously, we found that mutating the 4 TCF sites caused a reduction in enhancer activity ( 9 ). Mutating either one of the SOX sites caused a reduction in enhancer activity comparable to mutating the 4 TCF binding sites.…”
Section: Resultsmentioning
confidence: 99%
“… F) Cartoon of the c-Myc-335 enhancer showing positions of the newly identified SOX binding sites (purple) along with previously characterised TCF, CDX, and CAG sites ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations